VD_FINDINFO Jug / 2015 / 187 vom 19. Juni 2013 - VD Tribunal cantonal (2013)
TRIBUNAL FÉDÉRAL, INTERNEMENTDROIT PÉNAL, INDEMNITÉEN GÉNÉRAL | 64 al. 1 CP, 64 CP, 107 al. 2 LTF, 107 LTF, 429 al. 1 let. a CPP (CH), 429 CPP (CH)